Entrepreneurship among Low-, Mid- and High-Income Workers in South America: A Fuzzy-Set Analysis - Jorge Velilla; José Alberto Molina; Raquel Ortega (Institute of Labor Economics (IZA), 2020)
This paper studies the reasons underlying the entrepreneurial decisions of low-, middle-, and high-income workers in South America. Using data from the GEM APS for the period 2005-2017, we apply fuzzy set Qualitative Comparative Analysis, allowing us to find causal links in the form of necessary conditions linked to entrepreneurship in the sample countries. Results show some differences in the conditions that lead individuals to become entrepreneurs, depending on income levels and gender. However, peer effects, the social perception of entrepreneurship, entrepreneurial skills, and formal education seem decisive in different contexts, although they may operate in both complementary and substitutive ways. The same combination of conditions does not appear to work for all the countries, even when taking into account the gender and income level of workers.
Keywords: L26; J22; 330; South America; entrepreneurship; income; fsQCA; GEM data